Letters to Vasyl Sukhomlynskyi in Central State Archives of Supreme Bodies of Power and Government of Ukraine fonds as source from study of pedagogical everydayness - Sukhomlynska Olha; Sukhomlynska Lesia (Рукописна та книжкова спадщина України)

(untitled)
The goal of the research is to uncover the content of handwritten documents - letters from the archival collection of Vasyl Sukhomlynskyi, stored in the Central State Archives of Supreme Bodies of Power and Government of Ukraine. These letters reflect the pedagogical everyday life of the 1960s. The study’s methodology is based on historical-genetic, systemic, and micro-historical analysis, as well as socio-constructive and local pedagogical approaches to investigating recent history. These approaches are employed to realize the scientific novelty of the research, revealing the ‘history from below’ - the pedagogical realities contained in archival documents, which for the first time speak through the voices of direct participants in the educational process: teachers and parents. Conclusions. Letters addressed to Vasyl Sukhomlynskyi provide an opportunity to view pedagogical reality from the perspective of those (parents and teachers) who participate in or perceive socially constructed practices (the educational process) not passively but with emotional involvement, often voicing their objections to the dominance of official rules and regulations over children or individuals. The letters offered a means to clearly and vividly tell their own stories and the stories of their children, enriching the narratives with lively and specific examples. Addressed to Vasyl Sukhomlynskyi, these letters prompted him to use them extensively in his journalistic activities, helping him not only to affirm his personal humanistic and child-centered beliefs but also to formulate new ones.